Removal of Pb(II) from Aqueous Solutions Using Magnetic Mesoporous Silica Nanocomposites: Modeling and Optimization Based on Response Surface Methodology - Shokufe Emrani; Mahmoud Ebrahimi; Rahele Zhiani; Alireza Motavalizadehkakhky (آب و فاضلاب, 2023)
In the adsorption process of heavy metals, a major challenge is to design and develop adsorbent materials in an abundance of accessible adsorption sites with high affinity to achieve both fast adsorption kinetics and increased adsorption capacity for toxic contaminants. The removal of pollutants by mesoporous silica adsorbents is now in the limelight due to the nontoxicity and biocompatibility of these materials with the environment. In this study, a fibrous core-shell magnetic mesoporous composite (Fe3O4/SiO2/KCC-1) was successfully synthesized and used as a nano-adsorbent to remove Pb(II) from an aqueous solution. The adsorbent was characterized by employing TEM, SEM, FTIR, VSM, XRD, and N2 adsorption–desorption techniques. According to the results, Fe3O4/SiO2/KCC-1 was successfully synthesized with an average pore diameter of 7.94 nm, a surface area of 813.07 m2 g-1, and a pore volume of 1.41 cm3 g-1. The response surface methodology (RSM) was then adopted in the central composite design (CCD) to optimize parameters of the adsorption process. The optimal conditions for Pb(II) adsorption were then determined at a temperature of 80 °C, an adsorption dosage of 0.04 g L-1, a pH 5.6, and the contact time of 38 min. The removal rate of Pb(II) was 90%. Studies of equilibrium and kinetics indicated that the adsorption process followed Langmuir’s isotherm and the pseudo-first-order model with correlation coefficients of 0.98 and 0.99, respectively. The maximum adsorption capacity of Fe3O4/SiO2/KCC-1 was reported 574.4 mg g-1. Moreover, the thermodynamic parameters known as enthalpy (ΔH° = +5.84 kJ mol-1), negative Gibbs free energy (∆G°) values, and entropy (ΔS° = +23.42 kJ mol-1 K-1) indicated that the adsorption was endothermic and spontaneous with the increased disorder at the solid–liquid interphase.